Evidence that a locus for familial psoriasis maps to chromosome 4q. - Matthews, D; Fry, L; Powles, A; Weber, J; McCarthy, M; Fisher, E; Davies, K; Williamson, R (1996)
Psoriasis is an inflammatory skin disease that affects 2% of the population. It is characterised by red, scaly skin patches which are usually found on the scalp, elbows and knees, and may be associated with severe arthropathy. The lesions are caused by abnormal keratinocyte proliferation, and infiltration of inflammatory cells into the dermis and epidermis. The usual age of onset of psoriasis is between 15 and 30 years, although it can present at any age. Psoriasis is recognised to have a large genetic component. Twin studies show the concordance in monozygotic twins to be between 65-70%, compared to between 15-20% in dizygotic twins. Family studies estimate the risk to first degree relatives at between 8-23%. However, there are also several environmental factors, including streptococcal infection and stress, that affect the onset and presentation of the disease. The mode of inheritance of psoriasis is unclear. We conducted a genome-wide scan to search for psoriasis susceptibility loci in a single large multiplex family. Parametric linkage analysis indicated that a susceptibility locus for familial psoriasis was located on chromosome 4q. Investigation of this locus in five further multiplex families using both parametric and non-parametric methods gave significant localisation to chromosome 4q. The maximum total pairwise lod score obtained was 3.03 with the microsatellite marker D4S1535 at theta = 0.08. Non-parametric multipoint analysis with GENEHUNTER- demonstrated significant excess allele sharing, with a P value of 0.0026, at the same locus.